2014
DOI: 10.7860/jcdr/2014/6674.4108
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Neonatal Icter and Gilbert Syndrome in Gloucose-6-Phosphate Dehydrogenase Deficient Subjects

Abstract: Background and Aim: The pathogenesis of neonatal hyper bilirubinemia hasn't been completely defined in Gloucose 6 Phosphate Dehydrogenase (G6PD) deficient newborns. The aim of this study was to detect the relationship between Gilbert's syndrome and hyperbilirubinemia in Gloucose 6 Phosphate Dehydrogenase (G6PD) deficient neonates. Materials and Methods:This case control study was con ducted in Amirkola pediatrics teaching hospital, Babol, Iran. A total number of one hundred four infants were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…GS is caused by a mutation in the UGT1A1 gene resulting in impairment of glucuronidation of unconjugated bilirubin within hepatocytes. Several studies have reported the coexistence of GS and hereditary spherocytosis, G6PD deficiency, gallstone disease and other diseases ( 8 , 18 , 19 ). The reports were summarized in Table II for UGT1A1 genetic mutations and related diseases during the past 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…GS is caused by a mutation in the UGT1A1 gene resulting in impairment of glucuronidation of unconjugated bilirubin within hepatocytes. Several studies have reported the coexistence of GS and hereditary spherocytosis, G6PD deficiency, gallstone disease and other diseases ( 8 , 18 , 19 ). The reports were summarized in Table II for UGT1A1 genetic mutations and related diseases during the past 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that there is no significant relationship between Gilbert's syndrome (promoter polymorphism) and hyperbilirubinemia in G6PD deficient neonates. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the study of G6PDdeficient severe hyperbilirubinemia [35], G71R mutation in the experimental group was found to be higher than that in the control group, with a mutation rate of 55.1% and 25.0%, respectively, indicating that G71R Site mutation is a risk factor for severe hyperbilirubinemia in patients with G6PD deficiency. Fu Wenping et al [36] found that TATA box mutation was not associated with neonatal jaundice and G6PD deficiency in Guangxi; Zahedpasha et al [37] also found that promoter polymorphism was not associated with G6PD deficiency.…”
Section: G6pd Enzyme Deficiency Breast Milk Jaundice and Ugt1a1 Gene ...mentioning
confidence: 99%